In vitro growth responses of three varieties of rice (Oryza sativa) to eight potential plant growth-promoting rhizobacteria from Metroxylon sagu Rottb. - Pio, Doreen Mariz T. (2010)
The effect of eight local rhizospheric strains of bacteria, Rh1-MS-CO, Rh2-MS-CO, Rh3-MS-CO, Rh1-MS-MV, Rh2-MS-MV, Rh4-MS-MV, and RH5-MS-MV on the rice varieties Mestizo, Nipponbare, and IR-64 was investigated as well as the effect of Bio-N indole-acetic acid (IAA), and gibberellic acid(GA3). Seeds treatedwith Rh1-MS-MV and Rh2-MS-MV had the highest rate of germination. Seeds treated with 10ppm IAA had the most roots but Rh3-MS-MV had the highest number among the isolates. Rh2-MS-MV treated seeds grew the longest roots . Fort the shoot length, seedstreated with Bio-N had the longest shoots and Rh5-MS-MV among all bacterial treatments. For all four parameters there was a significant difference found between treatments. Only root length showed significant differences in the interaction of treatment and variety. For longest root length, Mestizo inoculated with Rh2-MS-MV had the highest means and shoot length, IR-64 and 10 ppm GA3 and for bacterial treatments, IR-64 and Rh5-MS-Mv. These are the recommended best combinations for longest root and shoot lengths. The isolates may be able to produce phytohormones to promote plant growth through increased germination rates, number of roots and root and shoot lenths, They show potential to be plant growth-promoting rhizobacteria. It is recommended to determine the identity of the isolates via molecular characterization and quantify the amount of phytohormone produced by the isolates.
Thesis (BS Biology) -- University of the Philippines Mindanao, 2010
Keywords: Rice; Nitorgen-fixing bacteria; Rhizosphere; Root growth; Rate of seed germination; Number of roots; Longest rooth length; Shoot length